Code-Mixing in Indonesian Selebgram’s Caption in Instagram (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
The use of code-mixing in any social media platform rises significantly. As one of currently popular social media, Instagram is mostly-found platform to mixing languages in users’ caption posts. Observing 10 captions written by an instagram-based influencer known with selebgram,, this study aims at (1) finding out code-mixing practices from the captions; and (2) classifying them into types of code-mixing based on Musyken’s theory. The captions were written by a celebrity, a trendsetter for Indonesian teenagers who use English as their target language. This study finds that (1) there are 10 code-mixing uses found in the 10 captions which are classified into (2) alternation type for 8 times, and congruent lexicalization type for 2 times.